Becoming Buddhist : experiences of socialization and self-transformation in two Australian Buddhist centres - Eddy, Glenys (Continuum advances in religious studies., 2012)
What does it mean to be a Western Buddhist? For the predominantly Anglo-Australian affiliates of two Western Buddhist centres in Australia, the author proposes an answer to this question, and finds support for it from interviews and her own participant-observation experience.Practitioners'' prior experiences of experimentation with spiritual groups and practices and their experiences of participation, practice and self-transformation are examined with respect to their roles in practitioners'' appropriation of the Buddhist worldview, and their subsequent commitment to the path to enlightenment.